2015
DOI: 10.1177/1071100715597657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arthroscopic Evaluation of Acute Ankle Fractures on PROMIS Intermediate-Term Functional Outcomes

Abstract: Level III, retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 24 publications
2
70
0
Order By: Relevance
“…study demonstrated that orthopedic surgeons are leading users of PROMIS measures. Orthopedic surgery contributed 9 publications on topics including fractures21 , chronic foot and ankle disorders[22][23][24] , sacral tumors 1,2 , ACL injury25 , and orthopedic trauma26 . One fracture study evaluated a percutaneous approach to acetabular fractures27 and the other evaluated the use of routine arthroscopy in the management of ankle fractures 21 .…”
mentioning
confidence: 99%
“…study demonstrated that orthopedic surgeons are leading users of PROMIS measures. Orthopedic surgery contributed 9 publications on topics including fractures21 , chronic foot and ankle disorders[22][23][24] , sacral tumors 1,2 , ACL injury25 , and orthopedic trauma26 . One fracture study evaluated a percutaneous approach to acetabular fractures27 and the other evaluated the use of routine arthroscopy in the management of ankle fractures 21 .…”
mentioning
confidence: 99%
“…In experienced hands, concomitant arthroscopy may only increase operative time by 15 to 20 minutes. 10 The techniques presented in this report are applicable to the sports, trauma, and foot/ankle surgeon.…”
Section: Discussionmentioning
confidence: 98%
“…6,7 Arthroscopic evaluation after ankle fracture shows a high prevalence of intra-articular pathology, although correlation with outcomes has been mixed. [8][9][10] There has yet to be an arthroscopic sign to characterize ankle instability intraoperatively. For the shoulder, the arthroscopic shoulder drive-through sign, originally reported by Pagnani and Warren, 11 is positive when the camera is easily passed between the glenoid and the humeral head into the anteroinferior joint space, which indicates laxity of the anterior capsule, usually after shoulder dislocation.…”
mentioning
confidence: 99%
“…Previous investigations have revealed associated osteochondral lesions in the majority of patients undergoing concomitant ankle arthroscopy at the time of fracture management, ranging upwards of 79%. 3,[7][8][9][10][11] These investigations have typically included heterogenous fracture types in their analyses, and results have indicated that certain injury patterns have a stronger correlation with intraarticular injuries, such as Weber B and C fibula fractures as well as those with syndesmotic injuries. 3,7,[9][10][11] The prevalence of intra-articular pathology in the cohort of Liu et al is lower than that which has typically been reported.…”
Section: See Related Article On Page 1714mentioning
confidence: 99%